Analyse de l’agentivité transformatrice dans une activité de robotique pédagogique impliquant la résolution collaborative de problèmes - Kamga, Raoul; Barma, Sylvie; Romero, Margarida (Canadian Journal of Education/Revue canadienne de l’éducation, 2023)
Collaborative problem solving is a very important skill for pre-service teachers. Indeed, they will be called upon to solve problems daily basis and to collaborate with other members of the school team or with their students. However, the collaborative problem-solving skill remains very little documented in the research. To contribute to the understanding of this skill, we will analyze it from a new angle, that of transformative agency, and in a context of educational robotics. We mobilize activity theory as a theoretical framework and analyze a pedagogical robotics activity involving a team of four pre-service primary teachers in collaborative problem solving. The results of our analyses highlight the presence of five of the six types of transformative agency expressions. They also highlight that the collaborative problem solving in this educational robotics activity was strongly marked by conflictual situations at the individual and collective levels.